MENINGKATKAN KEMAMPUAN MENGENAL BENTUK GEOMETRI MELALU PERMAINAN ENGKLEK PADA ANAK USIA 4-5 TAHUN DI KB PERMATA BUNDA KECAMATAN LUBUK DALAM KABUPATEN SIAK - Marmiati, Busri; Indarto, Wusono; Nurlita, Nurlita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : Background of this research is based on the observations madeby the author at the bottom of the KB Permata Bunda Lubuk Dalam subdistrictand Siak district, onje aspect of cognitive development that is pursued in earlychildhood is the familiar geometric shapes. Observer see that the average childin traffic recognize geometric shapes are still very low, only 8 of 17 children wereable to name and recognize geometric shapes. So that children feel confusion anddifficulty in playing. From these events, the authors are interested in performingan action that can improve cognitive abilities of children in the geometri shapes.Thus the authors are interested in doing this research to improving the ability oftitle game of hopscocth geometric shapes in children for 4-5 years in KB PermataBunda, Lubuk Dalam subdistric and Siak district. The study was conducted 17children. Place this research was carried out in KB Permata Bunda, LubukDalam subdistric and Siak district in children for 4-5 years. The study consistedof 2 cycles, and every cycle performed 3 sessions. Based on the analysis of thedata and see the results of the percentage increase in cycle I is 38,60% and oncycle II is 58,33%. Thus it can be said that assessment using a hopscotch gsmeimproves children’s ability to recognize geometric shapes for 4-5 years.Evidenced by the increase in the average value of each cycle and phenomenon ofgeometric shapes children’s cognitive ability, lesscreative teachers the ability todesign geometry know. Based on the analysis of data by looking at eachprogression with an increase in both enchancing the ability to recognize shapesthrough playing hopscotch geometry children for 4-5 years in KB Permata Bunda,Lubuk Dalam subdistric and Siak district.Keywords: The ability to recogninize throuometric shapes through playhopscotch.